(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Bioeconomy, which encompasses a broad scope of activity and can be terminologically explained in many ways, essentially contributes to the innovation, sustainability, economic growth and employment. The common features of cooperatives and bioeconomy are recognized, among other things, in the values such as equality, social responsibility, environmental protection, self-reliance, self-responsibility, democracy, etc. Cooperatives possess a social note, but the goal of their positioning as the creators of sustainability has to involve raising public awareness about what a sustainable cooperative business is. A cooperative is an association that puts people, environment, and social responsibility first, after the profit. The aim of the research was to identify the links between a cooperative business and bioeconomy in the function of sustainable rural development, thus identifying the characteristics and challenges of cooperatives in Osijek-Baranja County while proposing the measures for cooperative operations in the context of social economy. The paper analyses internal and external problems, such as institutional support, legal regulation, administrative measures, financial incentives, interpersonal relationships, educational structure etc. Based on the identified problem, a correlation between the given variables was investigated. Numerous experiences demonstrate that a cooperative, as a model of socially responsible entrepreneurship, ensures better living conditions and contributes to the overall and sustainable development of the European society. In Osijek-Baranja County, cooperatives have great significance, and although the number of cooperatives in the observed period (2011-2016) tends to fall, the total annual income of cooperatives and the number of employees tend to grow.